Landscape heterogeneity of peasant-managed agricultural matrices - Urrutia, Ana L.; González-Gónzalez, Cecilia; Van Cauwelaert, Emilio Mora; Rosell, Julieta A.; García Barrios, Luis; Benítez, Mariana (Agriculture, ecosystems & environment, 2020)
•Peasant agricultural landscapes in the tropics are characterized by high heterogeneity.•In the peasant landscape studied, agriculture constitutes a highly connected matrix.•Highly connected landscapes enable the coexistence of agriculture and conservation.•Subsets of heterogeneity metrics can help characterize and compare these landscapes. Management practices, environmental and social factors shape complex agricultural landscapes. In turn, the structure of such landscapes impacts biodiversity conservation, for instance, by mediating wildlife migration between agricultural and habitat patches and thus determining the persistence of metapopulations. Landscape ecology has used heterogeneity metrics and has systematically examined how they change with grain size and landscape extent to formally characterize a landscape, its structure and potential role in the persistence of wild metapopulations. These metrics provide valuable information regarding the landscape connectivity, patch diversity and shape. However, heterogeneity metrics have rarely been applied to tropical or subtropical, peasant-managed landscapes, even though this type of landscape occupies most of the agricultural surface in or near biodiversity hotspots. We focus on a peasant-managed agricultural landscape in Oaxaca, Mexico. For this landscape we mapped and quantified the land-use classes (48 % for agricultural land use, with kappa = 88.85 %). We also calculated heterogeneity metrics and examined their response to changes in grain and extent scales. This allowed us to further understand the structure and conservation potential of the agricultural matrix in this type of landscape, in comparison with other agricultural landscapes in Eastern North America. Our results also enabled us to recommend specific landscape metrics such as Largest Patch Index, Shape Index, and Interspersion & Juxtaposition Index, for different types of studies involving the link between agricultural matrices and conservation. We conclude that this type of agricultural matrix is ideal to pursue joint agricultural and conservation strategies in an integrated landscape.